Two-stage treatment of cholecystobronchial fistula secondary to gallbladder perforation: a case report - Wenbo Li; Liang Li; You Jiang; Jiayang Liu (Journal of Medical Case Reports)
Abstract Background Gallbladder perforation is a serious complication of acute cholecystitis. Among its rarest manifestations, cholecystobronchial fistula represents an exceptionally uncommon form of type III perforation and is frequently misdiagnosed due to its nonspecific presentation. Patient summary A 67-year-old Chinese (East Asian) male presented with a chief complaint of cough and hemoptysis. His medical history was significant for nephrotic syndrome, for which he had been receiving long-term corticosteroid therapy. Imaging demonstrated cholelithiasis, a cholecystobronchial fistula, and a right-sided lung abscess. A staged treatment approach was implemented. Stage I involved ultrasound-guided percutaneous transhepatic gallbladder drainage for infection control. Following clinical stabilization, stage II consisted of laparoscopic cholecystectomy. Intraoperative findings confirmed spontaneous closure of the fistula. The patient achieved an uneventful recovery and remained recurrence-free during follow-up. Conclusion Cholecystobronchial fistula typically results from chronic gallbladder inflammation. Prolonged corticosteroid use may obscure clinical manifestations, potentially delaying diagnosis. Contrast-enhanced computed tomography is essential for fistula identification, supplemented by bronchoscopic bilirubin or microbiological analysis. A staged minimally invasive approach enhances both safety and therapeutic efficacy. This report underscores the critical importance of multidisciplinary collaboration, precise imaging, and individualized surgical planning in the management of rare biliary fistulas.